Purification and characterization of polyphenol oxidase from corn tassel - Gul Guven, R.; Aslan, N.; Guven, K.; Matpan Bekler, F.; Acer, O. (Cellular and Molecular Biology, 2016)
In this study, polyphenol oxidase (PPO) from corn tassel  was extracted and partially purified through  (NH4)2SO4 precipitation and gel filtration chromatography. Optimal temperatures for subsrates catechol and 4-methyl catechol were 40 °C and 30 °C, respectively. The optimal pH values were 8.0 for catechol and 6.0 for 4-methyl catechol. Catechol was the most suitible substrate (Km: 3.48 mM, Vmax: 1.0 Abs./ min.). The moleculer mass of PPO was determined as 158 kDa. In this work, sodium azide, ethylenediaminetetraacetic acid (EDTA) and sodium dodecyl sulfate (SDS) were found to inhibit the enzyme activity as 26.6 %,  22.2 % and 12.2 % ratio, respectively. Besides, the effects of carbohydrates such as sucrose, fructose, ribose and glucose on PPO activity were investigated. The enzyme was found to be activated 17 % by fructose and ribose, 16 % by glucose and 4 % by sucrose.